Speckle imaging of graphene oxide and reduced graphene oxide - Sirikarntayuprakit, Pakkanhan; Yindeesuk, Witoon; Buranasiri, Prathan; Rattanasirawit, Chinnapat (My University, 2025)
Laser speckle imaging is a non-contact technique for analyzing materials' surface roughness and scattering characteristics. This study investigated the speckle patterns of graphene oxide (GO) in sheet form and reduced graphene oxide (rGO) in powder form under coherent laser illumination. The intensity distributions were recorded using a CMOS camera and analyzed statistically to determine key surface parameters, including speckle contrast and roughness. The results show that GO produces a finer, more uniform speckle pattern with lower contrast and roughness values than rGO, which exhibits coarser and more irregular patterns. These differences reflect the distinct structural characteristics of the two materials. The findings demonstrate the potential of speckle imaging for non-destructive optical characterization of graphene-based materials.
Keywords: graphene oxide; laser speckle; non-contact surface analysis; reduced graphene oxide; speckle contrast